Students’ Understanding of Student Well-Being: A Case Study - Falkenberg, Thomas; Ukasoanya, Grace; Krepski, Heather (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2021)
What does it mean for students to flourish (to be well) in school, what school ecology would this require, and what capabilities to live a flourishing life should schools help students develop? In this article, we report on a study that inquired into these three questions from the perspective of the students themselves, which is a perspective rarely inquired into. Data were collected from students at a large high school in Canada, using a survey (N = 50) and focus group interviews (N = 24). The findings provided diverse and rich student perspectives on the role that student well-being can and should play as an aim of school education.